EFFECT OF PH OF WELL WATER ON EFFICIENCY OF SOME INSECTICIDES UNDER FIELD CONDITION - Saddam mowafak Hassan; Nazar m. ALmallah (Mesopotamia Journal of Agriculture)
The result of used 6 well water in deiloution of 4 insecticides (salut, marshal, vapcotol and lannate) showed The values of Insecticides efficiency percentage were varied according to the well water kind and the time passed from the application date. The water of Gelbarat deep well reduce significantly the efficiency percentage of Salut to 49% and accelerate its degradation from 100% to 60, 47, 27, 14% after 1, 7, 14, 21 and 30 days from application, while xiluting marshal insecticides by the Gelbarat deep well water lead to produce ageneral mean efficiency reached 54% and reduce its field efficiency in controlling A phisrieri to 38%. The general mean efficiency percentage of vapcotal reached 60% when diluted by the water of Gelbarate deep well with a reduction in its efficiency reached 32% while lanate general mean efficiency reached 72% when diluted by Gelbarat deep well water which reduce its efficiency 22%.